2012
DOI: 10.1155/2012/702972
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Diabetes Mellitus: Association with Apolipoprotein E4 Polymorphism from a Hospital in Southern India

Abstract: Objective. To evaluate the association of Apolipoprotein E4 (ApoE4) in Alzheimer's dementia (AD) with comorbid diabetes mellitus (DM). Methods. The study included subjects with Alzheimer's dementia (AD) (n = 209), individuals with non-Alzheimer's dementia (nAD) (n = 122), individuals with parental history of AD (f/hAD) (n = 70), and control individuals who had normal cognitive functions and no parental history of dementia (NC) (n = 193). Dementia was diagnosed using International Classification of Diseases-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, these data do not rule out potential effects of APOE genotype on adipose tissue function, particularly in the context of metabolic challenges such as obesity or diabetes. In fact, several studies show that E4 exacerbates the severity of cognitive dysfunction and risk of dementia in patients with type 2 diabetes (Dore et al, 2003, Irie et al, 2008, Kota et al, 2012, Peila et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…However, these data do not rule out potential effects of APOE genotype on adipose tissue function, particularly in the context of metabolic challenges such as obesity or diabetes. In fact, several studies show that E4 exacerbates the severity of cognitive dysfunction and risk of dementia in patients with type 2 diabetes (Dore et al, 2003, Irie et al, 2008, Kota et al, 2012, Peila et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether diabetes and stroke act independently or synergistically with E4 as a risk factor for dementia. Previous studies of involvement of E4 and diabetes in AD indicate that the two factors in combination are a stronger risk factor than either factor alone, though it is not clear if they act synergistically [34,66,67]. Studies of the involvement of E4 and stroke in dementia are suggestive that the two factors act independently [68,69].…”
Section: Interactions Between Diabetes Stroke and E4 In Dementiamentioning
confidence: 99%
“…A study by Solanki et al [21] reported that 48% of DM patients had characteristics similar to dementia. Positive correlation between DM and dementia was further reported in another study where association of apolipoprotein E (APOE) genotype was also indicated [22]. In another study, Khattar et al [23] found cognitive decline in DM patients proving the link between DM and dementia.…”
Section: Relationship Between Diabetes and Dementiamentioning
confidence: 76%